2019
DOI: 10.2217/cer-2018-0134
|View full text |Cite
|
Sign up to set email alerts
|

Facing real-life with direct oral anticoagulants in patients with nonvalvular atrial fibrillation: outcomes from the first observational and prospective study in a Spanish population

Abstract: Aim: To analyze the effectiveness and safety of direct oral anticoagulants (DOACs) in atrial fibrillation (AF) patients attended in clinical practice. Methods: Observational and prospective study of AF patients that started treatment with DOACs. Results: 1443 patients (age 77.2 ± 9.7 years, CHA2DS2-VASc = 4.1 ± 1.5) were included. 46.0% were taking rivaroxaban, 24.4% dabigatran, 22.5% apixaban and 7.1% edoxaban. Patients taking dabigatran were younger, had lower CHA2DS2-VASc and lesser renal insufficiency. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
2
14
0
7
Order By: Relevance
“…Dosing of rivaroxaban, which is adjusted only according to kidney function, seems to be simpler than that of other DOACs, which is more limited by various factors (creatinine, weight, age, treatment with P-glycoprotein inhibitors). Consequently, prescribing this agent would reduce the risk of errors (Table 2) [5,[67][68][69][70], although dosing errors arising from the single criterion of kidney function have also been reported [71]. This is in line with different studies performed in real-life patients that have shown that despite rivaroxaban is underdosed in a significant proportion of patients, rates of thromboembolic and bleeding complications are low [72,73].…”
Section: Importance Of Appropriate Dosing Of Doacs In Elderly Patientsmentioning
confidence: 80%
See 1 more Smart Citation
“…Dosing of rivaroxaban, which is adjusted only according to kidney function, seems to be simpler than that of other DOACs, which is more limited by various factors (creatinine, weight, age, treatment with P-glycoprotein inhibitors). Consequently, prescribing this agent would reduce the risk of errors (Table 2) [5,[67][68][69][70], although dosing errors arising from the single criterion of kidney function have also been reported [71]. This is in line with different studies performed in real-life patients that have shown that despite rivaroxaban is underdosed in a significant proportion of patients, rates of thromboembolic and bleeding complications are low [72,73].…”
Section: Importance Of Appropriate Dosing Of Doacs In Elderly Patientsmentioning
confidence: 80%
“…Although both clinical trials and real-world studies have shown that DOACs have a better safety and efficacy profile than VKAs, a major problem observed in clinical practice is that of incorrect prescription that is prescribing a dose that is not consistent with the summary of product characteristics. Various studies performed in different clinical contexts have shown that inappropriate prescription of DOACs is not uncommon, especially underdosing [5,67,68]. Thus, the results of real-world studies have shown that inappropriate dosing of these drugs is common.…”
Section: Importance Of Appropriate Dosing Of Doacs In Elderly Patientsmentioning
confidence: 99%
“…We found only one study that included all four NOACs, in which no preference for one specific NOAC was found, except that rates of major bleeding were lower with rivaroxaban. 53 Of the 26 studies in which apixaban, rivaroxaban and dabigatran were included, apixaban was favourable compared with dabigatran and rivaroxaban in 13 studies, of which 10 were from the USA, 2 from Europe and 1 from Asia, 16 17 19 20 23 26 28 29 32 36 42 50 52 while dabigatran and rivaroxaban were not found to be the single most favourable NOAC in any of the remaining 13 studies. Results for these 13 studies were mixed, with either no favourable NOAC at all or one NOAC was selected as the least favourable, while the other two NOACs did not differ.…”
Section: Study Resultsmentioning
confidence: 98%
“…The most important differences between the studies are outlined in table 6. More than 50% of the studies were conducted in the USA (n=24), five were conducted in Denmark, [40][41][42][43][44] four in Taiwan, [45][46][47][48] and one in France, 49 Sweden, 50 Scotland, 51 the UK, 52 Spain 53 and China. 54 Dabigatran and rivaroxaban were included in all 39 studies, apixaban was included in 26 studies and edoxaban was included in 1 study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation